Rubric to evaluate the architecture project in the design workshop - Martínez Vitor, Cesar Fortunato (2021)
The perspective of Peruvian university educational model based on competencies leads to new educational procedures and their evaluation. The architectural professional career in its process of adaptation requires implementing these procedures. The evaluation of the performance process of architecture students, especially in design workshops, has the rubric as a qualitative instrument used to describe their performance. The analytical rubric to evaluate the architectural project competencies in the design workshop was the objective achieved. Due to its descriptive scope it was a qualitative research, testing the rubric through the valuation method. The rubric was applied in the project issues, the architectural research, the architectural program and the representation of the final project, of the Design Workshop 10 in 2017-2 semester of the Public University of the Center of Peru. The reliability and validity of the self-evaluation rubric (0.966 reliability), coevaluation (0.946 reliability) and heteroevaluation (0.8.89 reliability) in the project issues was demonstrated through descriptive statistics, through the performances to be evaluated, descriptors of the performance level, and assessment scales were related to the concepts, processes and representations of architecture, which allowed and solved the problem of evaluation the architectural project.